Chemical Components and Bioactive of Gorgonian Sea Plumes (Genus Rumphella and Hicksonella) from Raijua Islands-East Nusa Tenggara - Yunialdi Happynes Teffu; Ruddy Suwandi; Nurjanah Nurjanah (Jurnal Pengolahan Hasil Perikanan Indonesia, 2015)
Sea plumes is mostly used by people as jewellery and arthritis drug. The aim of this research was to characterize the chemicals and the bioactive compounds of the sea plumes for pharmaceutical ingredients. Characterization of sea plumes was carried out schlerit form identification, proximate analysis, heavy metal analysis using Atomic Absorption Spectrofotometer, radium content using gamma spectrometer, extraction by maceration method for 24 hour and phytochemicals quality testing based on color appearance. The sea plumes was identified as Rumphella and Hicksonella contains the highest protein components. Heavy metal Pb exceed the standar set to National Standar of Indonesia (SNI) and Medicines and Foods Security Agency. Akar bahar containing radium 0.65-0.79 Becquerel/kilogram, highest yield using methanol and containing secondary metabolite which targeted as bioactive compounds alkaloids, flavonoids, phenols hydroquinone, steroids, triterpenoids and saponins. Keywords : Hicksonella, secondary metabolite, radium, Rumphella, sklerit